84.5k views
0 votes
.............................................................................

.............................................................................-example-1
User Pauli
by
6.0k points

2 Answers

4 votes
(-2/3)*(5/4)

Note - multiplied by + = -.

2 into 4 is 2

(-2/3)*(5/4) = -(5)/(3*2) = -5/6



Product of -2 2/5 and -3 5/6

- 2 2/5 = - (2*5 + 2)/5 = - (10 + 2)/5 = -12/5 changed to improper fraction


- 3 5/6 = - (3*6 + 5)/6 = - (18 + 5)/6 = -23/6 changed to improper fraction


= (-12/5) * (-23/6) 6 into 12 is 2, - * - is +

= + (2*23)/5

= 46/5 5 into 46 is 9 remainder 1

= 9 1/5

Hope you find the explanation useful.
User Dhruvbird
by
5.8k points
5 votes
-6and 1 over 3 because of simplification
User Smoothumut
by
6.9k points